Cost effectiveness of the cancer prevention program for carriers of the BRCA1/2 mutation - Marcelo Cristiano de Azevedo Ramos; Maria Aparecida Azevedo Koike Folgueira; Simone Maistro; Alessandro Gonçalves Campolina; Patricia Coelho de Soárez; Geertruida Hendrika de Bock; Hillegonda Maria Dutilh Novaes; Maria Del Pilar Estevez Diz (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE: To analyze the cost effectiveness of the diagnostic program for the germline mutation in BRCA1/2 genes and of preventative strategies for the relatives of patients diagnosed with ovarian cancer associated with this mutation. METHODS: The study analyzed the cost effectiveness by developing an analysis of the Markov decision process from the perspective of the National Health System. The strategies compared reflect upon the adoption of genetic testing and preventative strategies for relatives or the usual care currently proposed. The incremental cost-effectiveness ratio was expressed in terms of cost per case avoided. The sensitivity analysis was performed in a univariate and deterministic manner. RESULTS: The study showed increments for effectiveness and for costs when performing genetic testing and adopting prophylactic measures for family members. The incremental cost-effectiveness ratio was estimated at R$908.58 per case of cancer avoided, a figure considered lower than the study's cost-effectiveness threshold (R$7,543.50). CONCLUSIONS: The program analyzed should be considered a cost-effective strategy for the national situation. Studies in various other countries have reached similar conclusions. One possible ramification of this research might the need to perform a budgetary-impact analysis of making the program one of the country's health policies.